APPLICATION OF ORGANIC WASTE AS RENEWAL TECHNOLOGY OF EARTHWORM CULTURED MEDIA - Qurrota A'yunin (Journal of Innovation and Applied Technology, 2016)
AbstractThe organic material has a major influence on the development of earthworm population because the organic material contained in the media is needed to continue living. Earthworm species are very potential to be developed is a kind of Lumbricus rubellus. Tofu dregswere chosen because it has a high protein content that can accelerate growth. In addition, the availability of raw material tofu dregs will facilitate cultivation of earthworms and sustainability of this activity given the Kediri district as one of the producers of tofu and will automatically donate a sizeable tofu waste. Further use of tofu waste as raw material for the cultivation of earthworm media intended to reduce the impact of environmental pollution which may occur from the waste production of tofu. Results of growth of earthworms on organic waste media (Tofu Dregs, cow manure, sawdust and soil) fermented influence on the growth of biomass of earthworms L. rubellus shown the best results with a tofu dregs of the media gain value by an average of 87.78 g with SD ± 5.87 and the value of the average productivity of 2.92 g / day with SD ± 0.19. Production of earthworms increased from the initial weight of 1 kg to 3 kg within ± 45 days maintenance.